2006
DOI: 10.1111/j.1365-313x.2006.02762.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome evolution in Arabidopsis/Brassica: conservation and divergence of ancient rearranged segments and their breakpoints

Abstract: Since the tetraploidization of the Arabidopsis thaliana ancestor 30-35 million years ago (Mya), a wave of chromosomal rearrangements have modified its genome architecture. The dynamics of this process is unknown, as it has so far been impossible to date individual rearrangement events. In this paper, we present evidence demonstrating that the majority of rearrangements occurred before the Arabidopsis-Brassica split 20-24 Mya, and that the segmental architecture of the A. thaliana genome is predominantly conser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 48 publications
4
54
0
Order By: Relevance
“…The absence of the genome triplication in Calepina and Conringia species (n 5 7, 8) suggested the placement of these genera outside the tribe Brassiceae (Lysak et al, 2005). Similar to the previous study, three different ancestral blocks (J, M, and N) were found to be triplicated in the B. oleracea (n 5 9) complement upon CCP analysis (Ziolkowski et al, 2006). Hence, cytogenetic data corroborate the results of genetic mapping studies and provide strong evidence for the occurrence of an ancient whole-genome triplication event defining the tribe Brassiceae as a natural monophyletic lineage (Lysak et al, 2005;Lysak and Lexer, 2006).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…The absence of the genome triplication in Calepina and Conringia species (n 5 7, 8) suggested the placement of these genera outside the tribe Brassiceae (Lysak et al, 2005). Similar to the previous study, three different ancestral blocks (J, M, and N) were found to be triplicated in the B. oleracea (n 5 9) complement upon CCP analysis (Ziolkowski et al, 2006). Hence, cytogenetic data corroborate the results of genetic mapping studies and provide strong evidence for the occurrence of an ancient whole-genome triplication event defining the tribe Brassiceae as a natural monophyletic lineage (Lysak et al, 2005;Lysak and Lexer, 2006).…”
supporting
confidence: 69%
“…Three homeologous copies of block F found in Brassiceae species studied herein are in agreement with genetic mapping data (Parkin et al, 2005, and refs. therein) and provide further evidence for the ancient triplication of the Brassiceae genomes as previously shown for ancestral block U in a number of Brassiceae taxa (Lysak et al, 2005) and for blocks J, M, and N in B. oleracea (Ziolkowski et al, 2006). .…”
Section: Discussionmentioning
confidence: 87%
“…The unexpectedly detected WGD shared by the diploid Australian crucifer species is analogous to the mesopolyploid whole-genome triplication discerned in the tribe Brassiceae by comparative genetic mapping (Lagercrantz and Lydiate, 1996;Parkin et al, 2005) and by comparative cytogenetic analysis (Lysak et al, 2005(Lysak et al, , 2007Ziolkowski et al, 2006). Several lineagespecific WGD events thus far documented across the angiosperms (Tang et al, 2008;Jaillon et al, 2009;Soltis et al, 2009) represent only the tip of the iceberg, as potential other WGD events remain uncovered.…”
Section: Mesopolyploid Wgdmentioning
confidence: 99%
“…In addition to the ancient paleopolyploidy events (a, b, and g WGD), a further peak at Ks = 0.38 (Figure 2; Supplemental Table 4) was found in the B. rapa distribution, representing the now well documented mesopolyploidy event (Parkin et al, 2005;Ziolkowski et al, 2006;Wang et al, 2011). Similarly, mixture model analyses of the Ks distributions of L. alabamica and C. sativa also revealed the presence of a major peak at Ks = 0.33 and 0.09, respectively ( Figure 2C), which represent the independent hexaploidy events experienced by these species (Haudry et al, 2013;Kagale et al, 2014).…”
Section: Neo/mesopolyploidy Eventsmentioning
confidence: 99%
“…The genome of A. thaliana revealed compelling evidence for remnants of at least three paleopolyploidy events, known as a, b, and g WGDs (Bowers et al, 2003), that are shared by all crucifer taxa (Haudry et al, 2013). Additionally, early comparative genetic mapping (Parkin et al, 2005) and cytogenetic studies (Lysak et al, 2005;Ziolkowski et al, 2006), as well as the recent whole-genome sequencing of Brassica rapa (Wang et al, 2011) have identified an additional later mesopolyploidy (wholegenome triplication) event in diploid Brassicas. Using Bayesian approaches and fossil information as age constraints, the age of the triplication event has now been estimated to be 22.5 million years (Beilstein et al, 2010).…”
Section: Introductionmentioning
confidence: 99%